Precursors of School Shootings - Harrington, Branden (2019)
This paper analyzes mass school shootings in the United States, stressing their root causes, indicators, demographics, and suggestive guidelines for preventable measures. Data draws associations between bullying, social dominance, and devalued masculinity amongst high school boys. Further, these trends emphasize homophobic harassment and the reassertion of lost dominance through violence. Moreover, research upholds media coverage and self-absorbed behavior as an additional precursor for inspired acts of malice. Journalistic representations of mass school shootings are identified as a source of motivation for vengeful and easily malleable youth. Studies also stress the importance of school inclusivity and interconnectedness, emitting a stark correlation to the level of violence in schools across America. In turn, applicable solutions are best represented by Effective Behavioral Support and violence prevention methods practiced by teachers and campus staff. In addition, school security upheld positive results as well, whether executed by armed guards or fencing